2011
DOI: 10.1016/j.toxicon.2011.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of purified Russell’s viper venom-factor X activator (RVV-X) on renal hemodynamics, renal functions, and coagulopathy in rats

Abstract: Acute renal failure (ARF) is the most frequent and a serious complication in victims of Russell’s viper snakebites. Russell’s viper venom-factor X activator (RVV-X) has been identified as a main procoagulant enzyme involving coagulopathy, which might be responsible for changes in renal hemodynamics and renal functions. Here, we purified RVV-X from crude Russell’s viper venom to study renal hemodynamics, renal functions, intravascular clot, and histopathological changes in Sprague–Dawley rats. Changes in renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…Since APC deficiency is associated with microvascular thrombosis and that DIC is always manifested with renal dysfunction (42), it is speculated that the occlusion of glomerular capillaries induced by DrKIn-I-mediated APC inhibition may be the cause of acute renal failure. Although it has been documented that RVV-induced renal failure may be due to the direct nephrotoxic components in the venom (43), other studies have shown that intravascular clotting and hemolysis may be the main cause of renal failures in these patients (44,45). In support of our hypothesis, it was found that none of the envenomed patients who did not develop DIC suffered from renal failures (46).…”
supporting
confidence: 83%
“…Since APC deficiency is associated with microvascular thrombosis and that DIC is always manifested with renal dysfunction (42), it is speculated that the occlusion of glomerular capillaries induced by DrKIn-I-mediated APC inhibition may be the cause of acute renal failure. Although it has been documented that RVV-induced renal failure may be due to the direct nephrotoxic components in the venom (43), other studies have shown that intravascular clotting and hemolysis may be the main cause of renal failures in these patients (44,45). In support of our hypothesis, it was found that none of the envenomed patients who did not develop DIC suffered from renal failures (46).…”
supporting
confidence: 83%
“…They suggested that the changes in hemodynamics were possibly caused by the presence of some proteolytic enzymes in the RVV although the RVV proteinase(s) actually responsible for this pharmacological effect was not identified by them. Later, it was reported that RVV-X is the key component that causes renal dysfunction and coagulopathy in experimental animals (Suntravat et al 2011). Changes in renal hemodynamics and renal functions such as decreased glomerular filtration rate (GFR), effective renal plasma flow (ERPF), effective renal blood flow (ERBF), and increased renal vascular resistance (RVR) suggested the formation of renal lesions due to RVV-X treatment in experimental animals (Suntravat et al 2011).…”
Section: Pharmacological Properties and Toxicity Of Rvv Proteinasesmentioning
confidence: 99%
“…Moreover, RV antivenom could also effectively prevent the D-dimer formation caused by purified RVV-X, under in vivo conditions when injected intravenously prior to RVV-X administration (Suntravat et al 2011). Further, no apparent histopathological changes in kidneys and lungs were observed in rats receiving RV antivenom along with purified RVV-X (Suntravat et al 2011). …”
mentioning
confidence: 96%
See 2 more Smart Citations